Childhood cancer registration in New Zealand: A registry collaboration to assess and improve data quality. (August 2018) - Ballantine, Kirsten R.; Hanna, Susan; Macfarlane, Scott; Bradbeer, Peter; Teague, Lochie; Hunter, Sarah; Cross, Siobhan; Skeen, Jane
Highlights: The completeness and accuracy of New Zealand child cancer registrations is high. Inclusion of non-resident cases and exclusion of non-malignant central nervous system tumours impacts upon child cancer incidence rates. Registry collaborative activities improves data quality and supports registrar training. Registry data can be used to assess and promote optimal patient referral pathways. Abstract: Aim: To evaluate the completeness and accuracy of child cancer registration in New Zealand. Methods: Registrations for children aged 0–14 diagnosed between 1/1/2010 and 31/12/2014 were obtained from the New Zealand Cancer Registry (NZCR) and the New Zealand Children's Cancer Registry (NZCCR). Six key data fields were matched using National Health Index numbers in order to identify and resolve registration discrepancies. Capture-recapture methods were used to assess the completeness of cancer registration. RESULTS: 794 unique cases were reported; 718 from the NZCR, 721 from the NZCCR and 643 from both registries. 27 invalid cancer registrations were identified, including 19 residents of the Pacific Islands who had travelled to New Zealand for treatment. The NZCCR provided 55 non-malignant central nervous system tumour and 16 Langerhans cell histiocytosis cases which were not registered by the NZCR. The NZCR alerted the NZCCR to 18 cases missed due to human error and 23 cases that had not been referred to the specialist paediatric oncology centres. 762 cases were verified as true incident cases, an incidence rate of 166.8 per million. Registration accuracy for six key data fields was 98.6%. According to their respective inclusion criteria case completeness was 99.3% for the NZCR and 94.4% for the NZCCR. For childhood malignancies covered by both registries, capture-recapture methods estimated case ascertainment at greater than 99.9%. CONCLUSION: With two national registries covering childhood cancers, New Zealand is uniquely positioned to undertake regular cooperative activities to ensure high quality data is available for research and patient care.